2013
DOI: 10.1177/0886260513506278
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Worlds of Bullies

Abstract: Research has yet to examine the social influences of parents, peers, and partners on bullying. This study explored the impact of social relationships on bullies, victims, bully/victims, and uninvolved participants. A sample of 370 college-age participants was asked about bullying, family environment, friends' illegal behavior, and conflict resolution tactics in romantic relationships. Results indicated controls came from more secure and engaged families. Bully/victims reported friends engaging in more illegal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…En esta investigación, al relacionar la disfuncionalidad familiar con el matoneo escolar, se evidenció que éstas son variables independientes; este resultado contrasta con el estudio realizado en Cali, en el que se encontró una asociación significativa entre ser víctima y reportar disfuncionalidad familiar leve y severa 35 . Otros estudios afirman que los niños víctimas de violencia familiar, también experimentan agresión en el colegio 37,38 En un estudio de casos y controles se indica que la poca seguridad, compromiso de la familia y preocupación entorno a esta predominaba en individuos que experimentaron acoso escolar (casos) 39 .…”
Section: Discussionunclassified
“…En esta investigación, al relacionar la disfuncionalidad familiar con el matoneo escolar, se evidenció que éstas son variables independientes; este resultado contrasta con el estudio realizado en Cali, en el que se encontró una asociación significativa entre ser víctima y reportar disfuncionalidad familiar leve y severa 35 . Otros estudios afirman que los niños víctimas de violencia familiar, también experimentan agresión en el colegio 37,38 En un estudio de casos y controles se indica que la poca seguridad, compromiso de la familia y preocupación entorno a esta predominaba en individuos que experimentaron acoso escolar (casos) 39 .…”
Section: Discussionunclassified
“…However regarding parenting style, some different results have been found on the part of bullies (Atik & Güneri, 2013; Keelan, Schenk, McNally, & Fremouw, 2014; Shin, Hong, Yoon, & Espelage, 2014). For example, findings showed that parents of bullies were low in affection and restriction (Atik & Güneri, 2013), and rejected their children more than uninvolved students (Keelan et al, 2014; Shin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, considering parenting styles of victimized children, research has generally produced mixed evidence. Most studies have emphasized that victimized children generally come from families with harsh parenting styles (Atik & Güneri, 2013; Batanova & Loukas, 2014; Bjorkqvist & Österman, 2014; Gómez-Ortiz et al, 2016; Keelan et al, 2014). For instance, physical punishment (Bjorkqvist & Österman, 2014), maternal psychological control (Batanova & Loukas, 2014), and parents’ low warmth (Atik & Güneri, 2013) have been identified as risk factors for children’s victimization at school setting.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to emotional security, relations are found between early attachment security and the quality of later peer relations, especially in middle childhood and adolescence (Pallini, Baiocco, Schneider, Madigan, & Atkinson, 2014; Schneider, Atkinson, & Tardiff, 2001). Suggesting relations between peer problems and diminished security about the family system as a whole, in a study based on a community sample, Keelan, Schenk, McNally, and Fremouw (2014) reported that bullys, bully/ victims, and victims had lower scores on emotional security about the family based on the SIFS compared to control/normative families.…”
mentioning
confidence: 99%